AB0313 Factors predicting disability in patients affected by long-standing rheumatoid arthritis treated with anti-TNF drugs: An observational study. (23rd January 2014) - Filippini, M.; Bazzani, C.; Atzeni, F.; Sarzi Puttini, P.; Marchesoni, A.; Favalli, E.; Caporali, R.; Cavagna, L.; Gorla, R.
Abstract : Background: HAQ (Health Assessment Questionnaire) is related to working ability, the need for specialist examinations and the quoad vitam prognosis; so it is an appropriate means of summarising outcomes, as well as the direct and indirect costs of the disease, as has been shown by pharmacoeconomic analyses. Moreover evenafter 20 years of treatment with traditional or biological DMARDs, joint damage evaluated using the Larsen and Sharp score isless than 40% of the highest possible score and the reversibility of the HAQ score is close to 70%even in the case of late arthritis. Objectives: This article describes the findings of an observational study designed to evaluate disability in patients with long-standing rheumatoid arthritis (RA) treated with anti-TNF agents. Theaims were to define the main predictors of disability during biological treatment and assess treatment strategies (the use of steroids and traditional DMARDs, a switch to another anti-TNF agent). Methods: The study involved 1033 patients attending six Italian rheumatology departments, who werestratified on the basis of various clinical and demographic variables. Drug effectiveness was assessed by analysing disease functional status using the Health Assessment Questionnaire (HAQ). Results: Disability significantly decreased after five years of anti-TNF therapy (ΔHAQ: -0.78, p<0.05). The HAQ improvement was less in patients aged >65 years, females, and those with a disease duration of more than 10 years, a higher comorbidity index, greater disease activity and disability at baseline, high titres of rheumatoid factor, and contraindications to combination therapy with traditional DMARDs. Steroids were useful in patients with greater baseline impairment. The patients treated with infliximab had a higher disability index at baseline, but showed greater improvement than those treated with etanercept or adalimumab. The results were confirmed by multivariate analysis. Conclusions: The effect of anti-TNF therapy on the disability of patients with long-standing RA is certainly substantial, and the HAQ is a good means of evaluating the efficacy of biological treatment. References: Aletaha D, Ward MM. Duration of rheumatoid arthritis influences the degree of functional improvement in clinical trials. Ann Rheum Dis. 2006; 65:227-33. Sokka T, Häkkinen A, Krishnan E, Hannonen P. Similar prediction of mortality by the health assessment questionnaire in patients with rheumatoid arthritis and the general population. Ann Rheum Dis. 2004; 63:494-7. Lloyd S, Bujkiewicz S, Wailoo AJ, Sutton AJ, Scott D. The effectiveness of anti-TNF-a therapies when used sequentially in rheumatoid arthritis patients: a systematic review and meta-analysis. Rheumatology 2010; 49:2313–21. Disclosure of Interest: None Declared